A Systematic Review of Occupational Exposure to Particulate Matter and Cardiovascular Disease - Shona C. Fang (International Journal of Environmental Research and Public Health, 2010)
Exposure to ambient particulate air pollution is a recognized risk factor for cardiovascular disease; however the link between occupational particulate exposures and adverse cardiovascular events is less clear. We conducted a systematic review, including meta-analysis where appropriate, of the epidemiologic association between occupational exposure to particulate matter and cardiovascular disease. Out of 697 articles meeting our initial criteria, 37 articles published from January 1990 to April 2009 (12 mortality; 5 morbidity; and 20 intermediate cardiovascular endpoints) were included. Results suggest a possible association between occupational particulate exposures and ischemic heart disease (IHD) mortality as well as non-fatal myocardial infarction (MI), and stronger evidence of associations with heart rate variability and systemic inflammation, potential intermediates between occupational PM exposure and IHD. In meta-analysis of mortality studies, a significant increase in IHD was observed (meta-IRR = 1.16; 95% CI: 1.06–1.26), however these data were limited by lack of adequate control for smoking and other potential confounders. Further research is needed to better clarify the magnitude of the potential risk of the development and aggravation of IHD associated with short and long-term occupational particulate exposures and to clarify the clinical significance of acute and chronic changes in intermediate cardiovascular outcomes.